Golden girl ebook - Hilderbrand, Elin (2021)
In this #1 bestselling page-turner from "the queen of beach reads" ( New York Magazine ), a Nantucket novelist has one final summer to protect her secrets while her loved ones on earth learn to live without their golden girl. On a perfect June day, Vivian Howe, author of thirteen beach novels and mother of three nearly grown children, is killed in a hit-and-run car accident while jogging near her home on Nantucket. She ascends to the Beyond where she's assigned to a Person named Martha, who allows Vivi to watch what happens below for one last summer. Vivi also is granted three “nudges” to change the outcome of events on earth, and with her daughter Willa on her third miscarriage, Carson partying until all hours, and Leo currently “off again” with his high-maintenance girlfriend, she’ll have to think carefully where to use them. From the Beyond, Vivi watches “The Chief” Ed Kapenash investigate her death, but her greatest worry is her final book, which contains a secret from her own youth that could be disastrous for her reputation. But when hidden truths come to light, Vivi’s family will have to sort out their past and present mistakes—with or without a nudge of help from above—while Vivi finally lets them grow without her. With all of Elin’s trademark beach scenes, mouth-watering meals, and picture-perfect homes, plus a heartfelt message—the people we lose never really leave us— Golden Girl is a beach book unlike any other.